THE IMPACT OF CRIME ON TOURISM VISITS IN CENTRAL JAVA: A PANEL DATA APPROACH - Rachman, Muhammad Aulia; Risanda A. Budiantoro; Syamsuddin (Universitas Negeri Semarang, 2025)
Crime generates insecurities, which limit tourism in several ways: reduced tourist destination appeal, increased perceptions of the risk of being victimized as a tourist, harm to destination image, increased transaction costs, and reduced institutional quality. This study employed a panel data approach to investigate the impact of criminal acts on tourist arrivals in 35 Central Javanese districts/cities from 2020 to 2024. Control variables included tourist attractions, accommodation, restaurants, vehicles, and the COVID-19 pandemic. Findings revealed a significant negative relationship between criminal cases and tourist visits, underscoring security's crucial role. Conversely, tourist attractions, accommodation, and restaurants positively affected arrivals. As expected, the COVID-19 pandemic negatively influenced tourism. Notably, the study found no significant impact from the prevalence of violence against children and women or the ratio of vehicles. Comparative analysis (between tourism-based and non-tourism-based regions) shows that crime consistently deters and attractions consistently promote tourism in all areas. Still, accommodation positively impacts tourism-based economies, while restaurants promote tourism in both regions. These results highlight the necessity of enhancing security measures at tourist destinations, fostering the development of sustainable attractions, and ensuring adequate supporting infrastructure to stimulate tourism sector growth in Central Java.